Radial velocity confirmation of K2-100b: a young, highly irradiated, and low-density transiting hot Neptune. Issue 1 (13th September 2019) - Barragán, O; Aigrain, S; Kubyshkina, D; Gandolfi, D; Livingston, J; Fridlund, M C V; Fossati, L; Korth, J; Parviainen, H; Malavolta, L; Palle, E; Deeg, H J; et al.
ABSTRACT: We present a detailed analysis of HARPS-N radial velocity observations of K2-100, a young and active star in the Praesepe cluster, which hosts a transiting planet with a period of 1.7 d. We model the activity-induced radial velocity variations of the host star with a multidimensional Gaussian Process framework and detect a planetary signal of 10.6 ± 3.0 ${\rm m\, s^{-1}}$,  which matches the transit ephemeris, and translates to a planet mass of 21.8 ± 6.2 M⊕ . We perform a suite of validation tests to confirm that our detected signal is genuine. This is the first mass measurement for a transiting planet in a young open cluster. The relatively low density of the planet, $2.04 _{ - 0.61 } ^ { + 0.66 }$  ${\rm g\, cm^{-3}}$, implies that K2-100b retains a significant volatile envelope. We estimate that the planet is losing its atmosphere at a rate of $10^{11}\!-\!10^{12}\, {\rm g\, s^{-1}}$ due to the high level of radiation it receives from its host star.